Immune cells in the pathogenesis of abdominal aortic aneurysm: Roles, regulation and targeted interventions - Junqi Peng; Hanqing Zhang; Yun Wu; Song Chen (Clinical and Translational Discovery, 2026)
Background Abdominal aortic aneurysm (AAA) is a lethal degenerative vascular disease with no approved clinical drugs. Immune responses dominate the entire AAA pathological process, and multiple immune cells regulate vascular homeostasis and disease progression via cytokine secretion. Methods This study systematically reviewed current literature to elaborate the infiltration and functions of macrophages, neutrophils and T cells in AAA, and summarized immune cell phenotypic imbalance and core regulatory mechanisms. Results We clarified the immune cell interaction network in AAA, generalized updated immune‐targeted intervention strategies, and sorted out major controversies in existing related studies. Conclusions This review highlights immune‐mediated AAA pathogenesis and research gaps, providing theoretical support for subsequent AAA basic research and novel immune‐targeted drug development.